Curing Opioid Toxicity with Intrathecal Targeted Drug Delivery - Thomas P. Pittelkow; Markus A. Bendel; Jacob J. Strand; Susan M. Moeschler (Case Reports in Medicine)
Pain is one of the most feared symptoms that concern cancer patients and their families. Despite well-established guidelines set forth by the World Health Organization (WHO) on the treatment of cancer pain, nearly half of cancer patients report poorly controlled pain. One of the most serious side effects of systemic oral opioid use is neurotoxicity, which is characterized by altered mental status and systemic neurologic impairments. Treatment strategies are supportive in nature and focused on reducing or changing the offending opioid and correcting any metabolic deficiencies. Herein, we discuss a case of opioid-induced neurotoxicity treated with intrathecal targeted drug delivery (TDD). The timing and implementation of advanced therapies such as intrathecal TDD is not well delineated. More importantly, patients and their oncologic providers are often unaware of this useful tool in treating challenging cancer-associated pain and significantly minimizing systemic opioid side effects. To ensure that patients have comprehensive oncologic care, best-practice guidelines suggest involvement of an interdisciplinary team and coordinated care. Early referral to a pain and palliative specialist may allow for improved patient outcomes and removal of unnecessary barriers to optimal patient care.